Multiple Clonostachys rosea UDP-Glycosyltransferases Contribute to the Production of 15-Acetyl-Deoxynivalenol-3-O-Glycoside When Confronted with Fusarium graminearum - Kelly A. Robinson; Antony D. St-Jacques; Sam W. Shields; Amanda Sproule; Zerihun A. Demissie; David P. Overy; Michele C. Loewen (Journal of Fungi, 2023)
Mycotoxins, derived from toxigenic fungi such as Fusarium, Aspergillus, and Penicillium species have impacted the human food chain for thousands of years. Deoxynivalenol (DON), is a tetracyclic sesquiterpenoid type B trichothecene mycotoxin predominantly produced by F. culmorum and F. graminearum during the infection of corn, wheat, oats, barley, and rice. Glycosylation of DON is a protective detoxification mechanism employed by plants. More recently, DON glycosylating activity has also been detected in fungal microparasitic (biocontrol) fungal organisms. Here we follow up on the reported conversion of 15-acetyl-DON (15-ADON) into 15-ADON-3-O-glycoside (15-ADON-3G) in Clonostachys rosea. Based on the hypothesis that the reaction is likely being carried out by a uridine diphosphate glycosyl transferase (UDP-GTase), we applied a protein structural comparison strategy, leveraging the availability of the crystal structure of rice Os70 to identify a subset of potential C. rosea UDP-GTases that might have activity against 15-ADON. Using CRISPR/Cas9 technology, we knocked out several of the selected UDP-GTases in the C. rosea strain ACM941. Evaluation of the impact of knockouts on the production of 15-ADON-3G in confrontation assays with F. graminearum revealed multiple UDP-GTase enzymes, each contributing partial activities. The relationship between these positive hits and other UDP-GTases in fungal and plant species is discussed.